PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MINIMARKET - Vincentius, Ade Arianto Cipto Putra (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this study was to determine how much and whether there is an influence between organizational culture, transformational leadership style and work motivation on the performance of minimarket employees. Data collection techniques are in the form of distributing questionnaires and literature study. The questionnaire was distributed to 100 employees who have different backgrounds, different working hours but have the same boss. In the research process, it is known that the effect of the independent variable on the dependent variable is 41.1%, while 58.9% is caused by other variables not included in the research framework.